Risk factors related to persistent airflow obstruction in severe asthma in Chinese Han population - Zhang, Lanlan (Int J Clin Exp Med, 2014)
Objective: To explore the significance of assessing persistent airway obstruction (PAO) in asthma patients by airway wall remodeling with bronchoscopy, high-resolution computed tomography (HRCT), and biological markers in the induced sputum and serum, exhaled nitric oxide (FENO), and lung function. Methods: The study was conducted in 119 patients with PAO and 125 patients with reversible airway obstruction (RAO). Endobronchial biopsy specimens were analyzed for airway smooth muscle (ASM) area, and reticular basement membrane (RBM) thickness. Airway thickness was also measured by HRCT scanning. Levels of matrix metalloproteases-9 (MMP-9), metalloproteinase 33 (ADAM33), and vascular endothelial growth factor (VEGF) were measured in the induced sputum and serum by enzyme linked immunosorbent assay. Result: PAO was associated with longer disease duration, absence of atopy and rhinitis, and larger ASM area (SMA%) (15.83%±2.32% [n=9] vs. 8.0%±1.68% [n=7], P=0.02), thicker RBM (16.27±2.32 μm [n=9] vs. 8.71±2.41 μm [n=7], P=0.042); No differences in any of the biomarker molecules measured in airway thickness in HRCT, sputum and blood individually between groups were found. Conclusion: Severe asthma patients with longer disease duration and the absence of atopy and rhinitis are more likely to develop PAO in Chines Han population. PAO patients have increased ASM area and RBM thickness appear to be valuable in the evaluation of airway remodeling in asthma patients in Chinese Han population.